Design and validation of a questionnaire on habits, health and exercise in the use of baby carriers - Yaiza Taboada-Iglesias; María del Carmen Iglesias-Pérez; Águeda Gutiérrez-Sánchez (Anales de Pediatría (English Edition))
Introduction: Understanding the characteristics and implications of the use of baby carriers can help health care providers understand the habits of their patients and provide guidance to improve quality of life in both children and caregivers. The aim of our study was to design and validate the first self-administered questionnaire to assess babywearing habits and their impact on health and physical activity as a means to monitor musculoskeletal complaints in caregivers. Material and methods: 350 individuals who currently used or had used baby carrying systems in the last 10 years completed the questionnaire, which was previously subject to a pilot study in a panel of experts. We used exploratory factor analysis to assess the validity of the internal structure of the questionnaire. The Cronbach α coefficient was used to assess reliability. We used varimax rotation to improve the interpretation of the extracted factors. Results: The factor analysis showed that the questionnaire is appropriate for measuring the dimensions or carriage factors established a priori. It extracted 3 factors each for the constructs of duration and weight of carriage, motivation, exercise habits and effects on infant health and 2 factors for caregiver pain that explained between 55% and 72% of the variance in each construct. The Cronbach α values were greater than 0.5. Conclusions: The results support the validity of the questionnaire and demonstrate that it is useful for its intended purpose. Resumen: Introducción: Conocer las características y las repercusiones del uso de portabebés puede ayudar a los servicios de salud a comprender los hábitos de sus pacientes y aportar consejo para mejorar la calidad de vida de niños y personas porteadoras. El objetivo de este estudio fue diseñar y validar la primera encuesta autoadministrada que mida los hábitos de porteo, y la repercusión que tienen para la salud y el ejercicio físico como medio de control de dolencias musculoesqueléticas de las personas cuidadoras. Material y métodos: 350 personas que utilizan o han utilizado en los últimos 10 años sistemas de transporte de bebés mediante porteo, completaron la encuesta, pilotada previamente en un panel de expertos. Se utilizó un análisis factorial exploratorio para obtener pruebas de la validez de la estructura interna de la encuesta. La fiabilidad fue evaluada mediante el coeficiente α de Cronbach. La interpretación de los factores extraídos se mejoró mediante la rotación varimax. Resultados: El análisis factorial mostró que el cuestionario es apropiado para medir las dimensiones o factores del porteo diseñadas a priori. Extrajo tres factores cada uno para los constructos de tiempo y carga del porteo, motivación, hábitos de ejercicio y efectos en la salud del bebé, y dos en relación al dolor de la persona cuidadora, que explicaban entre el 55% y 72% de la varianza en cada constructo. Los valores a α de Cronbach fueron superiores a 0,5. Conclusiones: Los resultados avalan la validez del cuestionario y que es útil para el objetivo propuesto.